2009
DOI: 10.1021/jf902005g
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Mechanism of a Novel Antifungal Protein from Pumpkin Rinds against Various Fungal Pathogens

Abstract: A novel antifungal protein (Pr-2) was identified from pumpkin rinds using water-soluble extraction, ultrafiltration, cation exchange chromatography, and reverse-phase high-performance liquid chromatography. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry indicated that the protein had a molecular mass of 14865.57 Da. Automated Edman degradation showed that the N-terminal sequence of Pr-2 was QGIGVGDNDGKRGKR-. The Pr-2 protein strongly inhibited in vitro growth of Botrytis cinerea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The lowest concentration of peptide that completely inhibited growth was defined as the minimal inhibitory concentration (MIC). Each MIC value was calculated as an average of independent experiments performed in triplicate [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The lowest concentration of peptide that completely inhibited growth was defined as the minimal inhibitory concentration (MIC). Each MIC value was calculated as an average of independent experiments performed in triplicate [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Black pumpkin seeds have another component, named cucurmoschin and identified as an antifungal peptide abundant in glycine, arginine, and glutamate residues. Additionally, Park and et al [133] found two novel antifungal proteins (Pr-1 and Pr-2) from pumpkin rinds that showed strong in vitro antifungal activity against Botrytis cinerea, Colletotrichum coccodes, Fusarium solani, F. oxysporum, and Trichoderma harzianum at 10-20 µM.…”
Section: Cucurbita Plants For Industrial Purposes: Key Role As a Foodmentioning
confidence: 99%
“…Lactobacilli strains can not only act against the growth of fungi, but can also act against the production of mycotoxins (Hudacek et al 2007). A series of studies on LAB indicated that some of the antifungal activity is caused by organic acids, low pH, proteinaceous compounds and other end products (Park et al 2009;Schnurer and Magnusson 2005;Hassan and Bullerman 2008). The antifungal protein produced by Enterococcus faecalis CHD 28.3 was partially purified by Roy et al (2009), the molecular mass of the antifungal protein from the high resolution gel filtration was estimated to be around 11 kDa.…”
Section: Discussionmentioning
confidence: 99%